Desarrollo de la ingeniería de detalle de un fotobiorreactor de panel plano para la generación de biomasa microalgal con un volumen de treinta litros (2019)
This work presents the development of detailed engineering for the design of a flat panel photobioreactor, taking as a starting point a volume of work, making use of complementary tools such as engineering software for computational fluid dynamics (CFD) and structural simulations . Based on the flow simulation for several proposed geometries, the most suitable for the photobioreactor was determined, and from this they designed and selected the components of the complementary systems of the equipment. For this it was necessary to define the models to be used for the simulations and the different parameters of these. Being a mechanical design process, the phenomena of the cultivation process were not taken into account at the time of the simulations. In addition, a selection was made of the necessary instrumentation elements for the acquisition of process data and the recording of changes in the process variables.